Interaction of sleep quality and anxiety on quality of life in individuals with type 2 diabetes mellitus - Dong, Dong; Lou, Peian; Wang, Jian; Zhang, Pan; Sun, Jianquan; Chang, Guiqiu; Xu, Chunrong (Health and quality of life outcomes, 2020)
Sleep disturbances and anxious symptoms are very common in people with type 2 diabetes mellitus(T2DM). This study aimed to assess the interactive effects of poor sleep quality and anxious symptoms on the quality of life of people with T2DM. Nine hundred and forty-four participants with T2DM were enrolled in a cross-sectional study. Demographic and physiological characteristics were recorded. Each participant completed a Chinese version of the Pittsburgh Sleep Quality Index, the Patient Health Questionnaire-9 and General Anxiety Disorder questionnaire, and the Diabetes Specificity Quality of Life scale. The products of poor sleep quality and anxiety were added to a logistic regression model to evaluate the multiplicative interactions, expressed as the relative excess risk of interaction, the attributable proportion of interaction, and the synergy index. Poor sleep quality and anxiety symptoms were associated with reduced quality of life. There was a significant interaction between poor sleep quality and anxiety symptoms; this combined effect significantly reduced quality of life scores by 6.09-fold. The relative excess risk of interactions was 1.36. The combined effect of poor sleep quality and anxiety symptoms reduces quality of life in people with T2DM. ChiCTR-IOP-16008045. Registered 3 March 2016. A clinical study to investigate gum infection in patients undergoing kidney dialysis.